2009
DOI: 10.1097/qai.0b013e31819c153f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Rapid Peer-Based HIV/AIDS Educational Intervention on Knowledge and Attitudes of High School Students in a High-Income Arab Country

Abstract: Grade 12 students' knowledge about HIV/AIDS was inadequate and attitudes stigmatizing. Peer-based knowledge workshops were effective, especially among females. Concise integrated teaching and workshops designed to address key knowledge and attitudinal deficiencies can be highly effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…These barriers need to be addressed urgently so that inmates can access VCT services in correctional centres. It is recommended that education and training as a tool to decrease HIV-related stigma is promoted in health care providers (Barss et al, 2009;Uys et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…These barriers need to be addressed urgently so that inmates can access VCT services in correctional centres. It is recommended that education and training as a tool to decrease HIV-related stigma is promoted in health care providers (Barss et al, 2009;Uys et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The other studies retrieved showed mixed results. For instance, a peer-led workshop on HIV/AIDS knowledge and attitudes was found less effective in men than in women [44]. Educational sessions were found effective in increasing knowledge, self-efficacy, behavior intention and/or self-reported behaviors in young boys who were involved in less risk (e.g.…”
Section: School-based Prevention Interventionsmentioning
confidence: 99%
“…Because of the composition of the student body at the Medical College of the UAE University, about 75% female, a field intervention survey was done by three female groups that visited girls' schools, and one group of males who went to boys' schools [14]; the study was performed by medical students, 75% of whom were female. Multistage stratified sampling was completed of government urban high-schools (10 female, 4 male schools in Al Ain, 4 female in Abu Dhabi), randomly selected from ministry lists.…”
Section: Population and Samplingmentioning
confidence: 99%
“…Sample size calculations [14] were completed separately for each medical student group, and for females with 3 groups they were conservative. A sample of 450 was sufficient to detect, with power of 80% and significance of 5%, an absolute difference in positive response to knowledge and attitude questions between subgroups of 15%, provided subgroup distribution was not skewed > 3 : 7.…”
Section: Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation